Pelatihan Peningkatan Sifat Individu Pendukung Kompetensi Petani Jagung Mandiri - Nurliza Nurliza (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2023)
TRAINING FOR IMPROVING PERSONAL TRAITS TO SUPPORT COMPETENCY OF CORN SMALHOLDERS. Corn smallholders frequently confront challenges in controlling and making appropriate farming decisions. They had low competence of farm management, smallholders intuitively emphasize the input cost aspect that causes high risk. The purpose of community service is conscientiousness, motivation, flexibility, positivity, and problem-solving of individual traits are increased using quantitative descriptive through counseling and practice for 20 corn smallholders of the "Sumber Lestari" farmer group in Rasau Jaya Village, Kubu Raya Regency, West Kalimantan as a corn integrated center area to accelerate the development of agribusiness-oriented agriculture. The findings revealed that corn smallholders had a high level of awareness and motivation. However, weather and disease concerns, as well as swings in the selling prices of products and production inputs, had reduced their flexibility, positivism, and problem-solving abilities. Personal traits are hopefully minimize the gaps between knowledge and skills. The role of local government is needed for sustainable monitoring, coaching, counseling and training, and disseminating research results that are responsive to changes in new innovations with a combination of visible and audible methods, as well as public meetings.